Network analysis of differential Ras isoform mutation effects on intestinal epithelial responses to TNF-α - Lau, Ken S; Schrier, Sarah B; Gierut, Jessica; Lyons, Jesse; Lauffenburger, Douglas A; Haigis, Kevin M (Integrative biology (Cambridge), 2013)
Tumor necrosis factor alpha (TNF-α) is an inflammatory cytokine that can elicit distinct cellular behaviors under different molecular contexts. Mitogen activated protein kinase (MAPK) pathways, especially the extracellular signal-regulated kinase (Erk) pathway, help to integrate influences from the environmental context, and therefore modulate the phenotypic effect of TNF-α exposure. To test how variations in flux through the Erk pathway modulate TNF-α-elicited phenotypes in a complex physiological environment, we exposed mice with different Ras mutations (K-Ras activation, N-Ras activation, and N-Ras ablation) to TNF-α and observed phenotypic and signaling changes in the intestinal epithelium. Hyperactivation of Mek1, an Erk kinase, was observed in the intestine of mice with K-Ras activation and, surprisingly, in N-Ras null mice. Nevertheless, these similar Mek1 outputs did not give rise to the same phenotype, as N-Ras null intestine was hypersensitive to TNF-α-induced intestinal cell death while K-Ras mutant intestine was not. A systems biology approach applied to sample the network state revealed that the signaling contexts presented by these two Ras isoform mutations were different. Consistent with our experimental data, N-Ras ablation induced a signaling network state that was mathematically predicted to be pro-death, while K-Ras activation did not. Further modeling by constrained Fuzzy Logic (cFL) revealed that N-Ras and K-Ras activate the signaling network with different downstream distributions and dynamics, with N-Ras effects being more transient and diverted more towards PI3K-Akt signaling and K-Ras effects being more sustained and broadly activating many pathways. Our study highlights the necessity to consider both environmental and genomic contexts of signaling pathway activation in dictating phenotypic responses, and demonstrates how modeling can provide insight into complex in vivo biological mechanisms, such as the complex interplay between K-Ras and N-Ras in their downstream effects.